Duo in a Mystical Realm—Nuclear Lipid Droplets and the Inner Nuclear Membrane. (December 2019) - Sołtysik, Kamil; Ohsaki, Yuki; Fujimoto, Toyoshi
The lipid droplet (LD) is a cytoplasmic organelle, but it also exists in the nucleus under some conditions or in some cell types. New studies have revealed that nuclear LDs do not occur by haphazard entry of cytoplasmic LDs. Instead, they are generated by specific mechanisms that are increasingly understood. The inner nuclear membrane (INM) plays a critical role in nuclear LD formation in both mammalian hepatocytes and budding yeast, although in significantly different ways. Hepatocyte nuclear LDs derive from precursors of very low-density lipoprotein lacking apolipoprotein B-100, which form in the endoplasmic reticulum lumen and accumulate in intranuclear extensions of the perinuclear space called type I nucleoplasmic reticulum. In contrast, nuclear LDs in yeast are generated by triglyceride synthesized in the INM. Nuclear LDs in hepatocytes and budding yeast are both instrumental in the regulation of phospholipid synthesis; however, again they function in different ways. As the full functional importance is as yet unknown, the close relationship of nuclear LDs and the INM is an attractive target of research from both physiological and pathological perspectives.